The effect of extensive reading on EFL students’ vocabulary size - Riyadh Ahsanul Arifin; Nguyen Ngoc Huy (Early Publishing Group, 2025)
This study examines the impact of extensive reading (ER) on vocabulary size among English as a Foreign Language (EFL) learners, highlighting the significance of vocabulary development as a core component of language fluency. While existing research underscores the benefits of ER in enhancing various language skills, there remains limited empirical evidence isolating its effect specifically on vocabulary size in structured, monitored contexts. The current state of the art emphasizes ER’s role in incidental vocabulary acquisition; however, few studies systematically measure vocabulary growth using quantifiable outcomes like vocabulary size before and after intervention. The primary aim of this research is to investigate whether sustained, extensive reading over a ten-week period significantly increases vocabulary size among EFL students. Employing a quasi-experimental design, the study involved 60 participants—divided equally into experimental and control groups—who were enrolled in intermediate English courses at a private Indonesian university. Data collection involved pre- and post-tests measuring vocabulary size, alongside reading logs to monitor reading volume. Data analysis was conducted using independent samples t-tests to compare vocabulary gains between groups and Pearson correlation analyses to explore the relationship between reading volume and vocabulary growth. Findings revealed that the experimental group demonstrated a statistically significant increase in vocabulary size compared to the control group. A positive correlation was identified between the amount of reading and vocabulary gains, supporting the hypothesis that increased reading volume facilitates lexical development. These results underscore the effectiveness of ER as a pedagogical approach that fosters natural vocabulary acquisition, especially when integrated consistently into language curricula. The study suggests that educators should emphasize extensive reading practices to enhance vocabulary development, thereby improving overall language proficiency. Future research could explore long-term retention and expand to diverse learner populations, providing broader insights into ER’s role in language learning.